2014
DOI: 10.1097/cco.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Update on testicular germ cell tumors

Abstract: Treatment paradigms continue to be refined for TGCTs as research in these areas continues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Furthermore, genome wide association studies identified a number of single nucleotide polymorphisms (SNPs) associated with TGCT, suggesting a strong genetic component for this cancer (Rapley et al 2009, Nallu et al 2014, Litchfield et al 2015, Rajpert-De Meyts et al 2016. These new TGCT susceptibility loci contain biologically plausible genes encoding proteins important for male germ cell development, chromosomal segregation and the DNA damage response (Koster et al 2014, Rajpert-De Meyts et al 2016.…”
Section: :3mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, genome wide association studies identified a number of single nucleotide polymorphisms (SNPs) associated with TGCT, suggesting a strong genetic component for this cancer (Rapley et al 2009, Nallu et al 2014, Litchfield et al 2015, Rajpert-De Meyts et al 2016. These new TGCT susceptibility loci contain biologically plausible genes encoding proteins important for male germ cell development, chromosomal segregation and the DNA damage response (Koster et al 2014, Rajpert-De Meyts et al 2016.…”
Section: :3mentioning
confidence: 99%
“…Testicular germ cell tumors (TGCTs) are the most frequent solid malignancy in young men aged between 15 and 35 years. Most of TGCTs are sporadic, but the heritability is high, and positive family history represents a well-established risk factor (Nallu et al 2014, Rajpert-De Meyts et al 2016. Other known risk factors are a prior TGCT, infertility, cryptorchidism and testicular microlithiasis (Nallu et al 2014, Rajpert-De Meyts et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation